Electrophysiological measures of conflict detection and resolution in the Stroop task - Coderre, Emily L.; Conklin, Kathy; van Heuven, Walter J.B. (Elsevier, 2011)
Conflict detection and resolution is crucial in a cognitive task like the Stroop task. Previous studies have identified an early negativity component (Ninc) as a prominent marker of Stroop conflict in event-related potentials (ERPs). However, to what extent this ERP component reflects conflict detection and/or resolution is still unclear. Here, we report a Stroop task in which the stimulus onset asynchrony (SOA) of color and word stimuli presentation was manipulated in order to disentangle the roles of conflict detection and conflict resolution in generating Stroop-related ERP components. Separating the word from the color information gives us precise control over the timing of conflict. If the Ninc is related with conflict resolution it should be absent when the word appears during response preparation, as in a long-latency positive SOA. Our data shows that the Ninc occurs in all SOAs, even after a response has been made, supporting its role in the detection of stimulus conflict rather than conflict resolution. The use of SOA manipulation therefore allows for the examination of a wider temporal spectrum of interference in order to specify the functions of this conflict-related component. These results provide insight into the neural signatures of conflict processes, and have implications for models of cognitive control mechanisms in the brain.